Sistematización de las actividades desarrolladas en el proceso de enseñanza aprendizaje en la práctica docente en la Unidad Educativa Víctor León Vivar, del cantón Nabón, provincia del Azuay, Ecuador, periodo lectivo 2019 2020 - Aguilar Guichay, Javier Gonzalo (2021)
Resumen:Research work entitled, systematization of the activities carried out in the teaching process learning in teaching practice in the Educational Unit "Víctor León Vivar", canton Nabón, province of Azuay, teaching period 2019-2020, raised as a general objective: to evaluate the results of teaching practice from the analysis of the stages of the teaching process, activities and resources as elements of the class plan to reorient , inform and innovate your professional performance. For the collection of information, collection and analysis of theoretical information was used through the elaboration of content sheets, extracted from different bibliographic sources and the analysis of the content of eight teaching plans. It is concluded that, in the systematized planning, the process of critical thinking (anticipation, development and consolidation) has been followed, which has been fulfilled, but there have been some successes and errors, both in planning and in the development of the practice. Teachers are recommended to improve the structure of planning and, in turn, its development in the teaching-learning process within the classroom.